Cointegration and Structural Breaks in the EU Sovereign Debt Crisis - Ferreira, N. B.; Menezes, R.; Bentes, S. (International Journal of Latest Trends in Finance and Economics Sciences, 2014)
First signs of a sovereign debt crisis spread among financial players in the late 2009 as a result of the growing private and government debt levels worldwide. Late 2010, Trichet (then President of the ECB) stated that the sovereign debt crisis in Europe had become systemic. In an established crisis context, it was searched for evidence of structural breaks and cointegration between interest rates and stock market prices. A 13 year time-window was used in six European markets under stress. The results identified significant structural breaks at the end of 2010 and consistently rejected the null hypothesis of no cointegration.